The patterns of consumption in visa-free zones at Russia’s western borders - Markku Sippola; Stanislaw Domaniewski (The Geographical Society of Northern Finland, 2014)
This article looks into habits of consumption on Russia’s western border areas. After the description of current consumption patterns, we discuss the involvement of Russian shoppers into “consumption culture”, theorised by Zygmunt Bauman. The empirics of this study cover the newly opened visa-free zones on border areas of the North-West Russia. We assume that in the long run an imbalance between shopping habits of corresponding nationalities will decrease. The “contagion” that now is occurring in the sphere of consumption will give rise to analogous contagions in the spheres of culture, work and social life. Furthermore, the establishment of a visa-free zone between the countries might provide an effective means to reduce the risk of so-called “border paradox” to occur.